Pharmacological characterization of noradrenaline-induced contractions of the porcine isolated palmar lateral vein and palmar common digital artery. - Blaylock, N A (1995)
1. The aim of this study was to examine the pharmacological characteristics of alpha-adrenoceptor-mediated contractions in two porcine isolated blood vessels, the palmar lateral vein (PLV) and the palmar common digital artery (PCDA). This was carried out with noradrenaline used as the agonist throughout, and either phentolamine (non-selective alpha-adrenoceptor antagonist), prazosin and YM-12617 (selective alpha 1-adrenoceptor antagonists) or rauwolscine and CH-38083 (selective alpha 2-adrenoceptor antagonists). 2. Noradrenaline (0.003-10 microM) produced concentration-dependent contractions in both vessels, with the PCDA (pD2 = 6.33 +/- 0.07, n = 10) being approximately 10 fold less sensitive to noradrenaline compared to the PLV (pD2 = 7.39 +/- 0.09, n = 8). Also, the maximal response to noradrenaline was greater in the PCDA compared to the PLV. Phentolamine (0.03-30 microM) produced parallel rightward shifts in the CRC to noradrenaline in both tissue preparations. The pA2 values were similar and slopes of the Schild plots were not significantly different from unity, indicating an interaction between phentolamine and a single receptor in each preparation. 3. In the PCDA the alpha 1-adrenoceptor antagonists, prazosin (0.01-1 microM) and YM-12617 (0.01-1 microM) produced non-parallel rightwards shifts in the CRC to noradrenaline, with the lower 10-15% of the CRC exhibiting greater resistance to the effects of these antagonists compared to the upper part. In contrast, rauwolscine (1-10 microM) and CH-38083 (10 microM) produced parallel displacement of the CRC to noradrenaline.(ABSTRACT TRUNCATED AT 250 WORDS)